Development of Story-Based Modules on Living Peacefully with Noble Morals - Narhaida, Nasira; Handayani, Sri; Marwiyah, St. (South Sulawesi Education Development (SSED), 2024)
This study aims to examine the development stage of story-based modules in learning peaceful living material with commendable morals for grade VII students at State Junior High School 13 Palopo, and evaluate the feasibility of the module. This research uses a research and development approach with research subjects totaling 19 grade VII students. The object of research is the Islamic religious education module on living peacefully with noble morals. The data collection techniques used are learning media validation sheets and questionnaires, while data analysis is carried out in a qualitative descriptive and quantitative descriptive manner. The results showed that the story-based module development stage followed the ADDIE approach, which included needs and curriculum analysis, module manufacturing design, preparation and manufacture of teaching materials, application of modules according to learning objectives, and evaluation of developed products. The feasibility of this module is evaluated by expert validators of the material and media, which gives very valid results. The implication of this research is the importance of developing story-based modules for learning peaceful living material with commendable morals in schools. The proposed recommendation is to increase the use of this module in the learning process, and further research needs to be carried out to measure the impact of using the module on the understanding and application of students' moral values.